A Response to Anna Kristina Hultgren’s Position Paper - Phillipson, Robert (Nordic Journal of English Studies, 2020)
I am grateful to Anna Kristina Hultgren for launching a debate on these important issues, and giving me an opportunity to contribute. Hultgren’s argument suffers, in my view, from a failure to define global English stringently or even to specify what specific characteristics of the use of the language she is most concerned about. Her essay raises many important issues, but each is in brief summary form. It strikes me as academic discourse that remains detached from the existential challenges that most work in language education and language policy engages in. What Hultgren refers to as applied linguistics (which is inexplicably capitalised, unlike other disciplines that the text refers to) is not rigorously specified. Nor is social justice exemplified or defined. Some of her argumentation consists, in my view, of dubious over-generalisations—which I will exemplify—embedded within pretty robust denunciations of applied linguists who are caricatured as out to ‘save’ and ‘salvage’ the world, no less!